Restriction genes for retroviruses influence the risk of multiple sclerosis. - Bjørn A Nexø; Bettina Hansen; Kari K Nissen; Lisa Gundestrup; Thorkild Terkelsen; Palle Villesen; Shervin Bahrami; Thor Petersen; Finn S Pedersen; Magdalena J Laska (PLoS ONE, 2013)
We recently described that the autoimmune, central nervous system disease, multiple sclerosis (MS), is genetically associated with the human endogenous retroviral locus, HERV-Fc1, in Scandinavians. A number of dominant human genes encoding factors that restrict retrovirus replication have been known for a long time. Today human restriction genes for retroviruses include amongst others TRIMs, APOBEC3s, BST2 and TREXs. We have therefore looked for a role of these retroviral restriction genes in MS using genetic epidemiology. We here report that markers in two TRIMs, TRIM5 and TRIM22 and a marker in BST2, associated statistically with the risk of getting MS, while markers in or near APOBEC3s and TREXs showed little or no effect. This indicates that the two TRIMs and BST2 influence the risk of disease and thus supports the hypothesis of a viral involvement.